Corporate Culture In Bumiputra And Non-Bumiputra Dominant Organization - Gan, Rubee Hui Cheng (1999)
The study attempts to explain the effects and consequences of organizational motivations, decision making, leadership, communication, management and the quality of working life. This study is expected to determine if there are similarities and differences between non-bumiputra and bumiputra dominant organizations' corporate culture. A total of 65 participants were randomly chosen. A 65 numbered questionnaire were used to gather the data required and tabulated using statistical package analyzing the 4 dimension (Hofstede's). The findings show that (i) bumiputra dominant organizations has low Power Distance, strong Uncertainty Avoidance, Individualism and Masculinity; (ii) non-bumiputra dominant organizations have low Power Distance, weak Uncertainty Avoidance, Individualism and Feminism and (iii) bumiputra dominant organizations and non-bumiputra dominant organization both has low Power Distance, Individualism but differs in terms of Uncertainty Avoidance and Masculinity. Bumiputra dominant organizations are collective than non-bumiputra organizations.